Phosphate and ammonium sorption capacity of biochar and hydrochar from different wastes. (February 2016) - Takaya, C.A.; Fletcher, L.A.; Singh, S.; Anyikude, K.U.; Ross, A.B.
Abstract: The potential for biochar and hydrochar to adsorb phosphate and ammonium is important for understanding the influence of these materials when added to soils, compost or other high nutrient containing environments. The influence of physicochemical properties such as mineral content, surface functionality, pH and cation exchange capacity has been investigated for a range of biochars and hydrochars produced from waste-derived biomass feedstocks. Hydrochars produced from hydrothermal carbonisation at 250 °C have been compared to low and high temperature pyrolysis chars produced at 400–450 °C and 600–650 °C respectively for oak wood, presscake from anaerobic digestate (AD), treated municipal waste and greenhouse waste. In spite of differences in char physicochemical properties and processing conditions, PO4 –P and NH4 –N sorption capacities ranged from about 0 to 30 mg g −1 and 105.8–146.4 mg g −1 respectively. Chars with high surface areas did not possess better ammonium adsorption capacities than low surface area chars, which suggests that surface area is not the most important factor influencing char ammonium adsorption capacity, while char calcium and magnesium contents may influence phosphate adsorption. Desorption experiments only released a small fraction of adsorbed ammonium or phosphate (<5 mg g −1 and a maximum of 8.5 mg g −1 respectively). Highlights: Biochars and hydrochars possess similar sorption capacities. Physisorption is not the dominant mechanism for NH4 -N uptake. PO4 -P uptake is best described by pseudo-second order kinetics.